Pelatihan Pembuatan Media Pembelajaran Fisika Berbasis ICT bagi Guru di Kabupaten Bengkayang, Kalimantan Barat - Nurussaniah Nurussaniah; Anita Anita; Boisandi Boisandi; Dwi Fajar Saputri; Eti Sukadi; Ira Nofita Sari; Matsun Matsun; Nurhayati Nurhayati; Lia Angraeni; Lukman Hakim; Wahyudi Wahyudi (Jurnal Pengabdian Pada Masyarakat, 2020)
TRAINING ON MAKING ICT-BASED PHYSICS LEARNING MEDIA FOR TEACHERS IN BENGKAYANG REGENCY, WEST KALIMANTAN. Improving learning quality is a crucial factor in the implementation of learning in schools to colleges. ICT contributes greatly to the dissemination of information materials to the world. It is one of the foundations of how important it’s to introduce and train teachers on the border to be proficient in information and communication technologies. The purpose of this activity is to train physics teachers in Bengkayang Regency to make ICT-based physics learning media. The goal of this dedication is teachers of physics that are incorporated in the MGMP Physics Regency of Bengkayang, West Kalimantan. The activity is located at SMAN 1 Bengkayang. This activity starts from the preparation phase of the situation analysis and problem of the partner and administration and coordination management with partners. Furthermore, at the stage of implementation of activities conducted is to provide mentoring to the partners through the training activities of ICT-based physics learning media generation. Steps at this stage include the introduction of ICT-based learning media, ICT-based physics media-making workshops and worksheet-making workshops as complementary media usage. The final stage is the evaluation of measuring the level of understanding and skills of participants after taking the training obtained from pretest, postest and observation sheet and designing the sustainability of the training program. From PKM activities that have been conducted, the planning and utilization training of ICT-based media learning for physics teachers in Bengkayang Regency, it can be concluded that the resource capacity is the teacher has increased. It is characterized by increased understanding of teachers about ICT-based learning media that can be used in teaching physics. In addition, teachers have been able to use Phet Simulation media and have been able to create Android applications on the concept of physics.